2007
DOI: 10.1002/pam.20309
|View full text |Cite
|
Sign up to set email alerts
|

The negative impacts of starting middle school in sixth grade

Abstract: Using administrative data on public school students in North Carolina, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 28 publications
6
59
7
Order By: Relevance
“…This lends further support to the idea that middle school attendance may be worse for students who enter at younger ages. Cook et al (2008) come to a similar conclusion, and hypothesize that younger students may be more sensitive to negative influences of older students.…”
Section: Checks On Robustness and Interpretationmentioning
confidence: 71%
See 2 more Smart Citations
“…This lends further support to the idea that middle school attendance may be worse for students who enter at younger ages. Cook et al (2008) come to a similar conclusion, and hypothesize that younger students may be more sensitive to negative influences of older students.…”
Section: Checks On Robustness and Interpretationmentioning
confidence: 71%
“…2 The impact of grade configuration has received little attention by economists relative to issues such as class size or teacher quality. There are a few studies which provide evidence that the transition to middle school is associated with a loss of academic achievement, elevated suspension rates, and reduced self esteem (Alspaugh (1998a(Alspaugh ( , 1998b, Weiss and Kipnes, (2006), Byrnes and Ruby (2007), Cook et al (2008)). There is also a large body of work by educational researchers and developmental psychologists documenting changes in attitudes and motivation as children enter adolescence (Eccles et al (1984)), and some have hypothesized that instructional differences in middle schools contribute to these changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental psychologists have documented a decline in achievement-related attitudes and beliefs among students transitioning to middle schools, which some have attributed to a mismatch between the motivational and developmental needs of early adolescents and aspects of the organizational environment in middle schools (Eccles and Midgley 1989). Studies using cross-sectional data have likewise shown that middle school transitions are associated with increased behavioral problems and declines in academic achievement (Allspaugh 1998, Byrnes and Ruby 2007, Cook et al 2008), but these findings could reflect unobserved differences between students attending schools with different grade configurations. Using panel data on American school districts, Bedard and Do (2005) show that increases in the share of 6 th graders enrolled in middle schools were associated with small decreases in graduation rates for the relevant cohorts.…”
Section: Background and Evidence On Grade Configuration In The Usmentioning
confidence: 99%
“…One commonly cited potential mechanism for the middle school achievement dip is the top dog/bottom dog (TDBD) phenomenon (Blyth, Simmons, & Bush, 1978;Cook, MacCoun, Muschkin, & Vigdor, 2008;Weiss & Kipnes, 2006), which occurs when students at the top of a grade span distribution have better experiences than those at the bottom. That is, the oldest students in a school (''top dogs'') experience a more favorable school environment (including increased participation in leadership roles and decreased incidence of bullying and fights) than the youngest students in a school (''bottom dogs''), who face increased victimization, exposure to delinquent peer influences, and feelings of anonymity.…”
Section: Introductionmentioning
confidence: 99%